Effectiveness of Horizontal Sub-drain to Increase Slope Stability with Vertical Cracks and Weathering Soil in Areas with High Rainfall Intensity - Putu tantri Kumala sari; Indrasurya B. Mochtar; Salisa Chaiyaput (My University, 2022)
Abstract A landslide occurred a few meters from the foot of the power plant tower in a hilly area in the Tulakan District, Pacitan, East Java Province, Indonesia. This incidence occurred after the area was flooded with a cumulative intensity of more than 1000 mm in one month and a maximum daily rainfall above 300 mm. Previous reports considered horizontal sub-drain cost-effective to reduce the groundwater level and the impact of rainwater seepage into the soil on slope stability. Therefore, this study aims to determine the effectiveness of horizontal sub-drain as an alternative for managing groundwater and rainwater that seeps into the soil to increase the slope factor of safety. The effect of real-time rainfall for 30 days before the landslide, hydraulic conductivity, changes in soil parameters due to cracking and weathering, and the existing groundwater level are also considered. The analyses were carried out using the coupled program SEEP/W for transient seepage and SLOPE/W with finite element method and limit equilibrium. The result showed that horizontal sub-drain increases the slope factor of safety from critical limit to more than 1.1 in 30 days of rainfall in high ground water level condition. The hydraulic conductivity parameters of the soil, the location of the horizontal sub-drain, as well as the cracked and weathered conditions in the soil also affect the effectiveness. In low-level ground water conditions, the duration of the rain and the intensity of the rain also greatly affect the effectiveness of the horizontal sub-drain as well as the number of cracks. In this condition, the safety factor on the slope with the horizontal sub-drain can increase the safety factor from less than one to more than one thus the slope becomes more stable. The results of this study also show that the effectiveness of the horizontal sub-drain is very sensitive to many things, therefore in its planning it is necessary to review many aspects more carefully.
Keywords: Rainwater Harvesting; Intensity; Soil and Unsaturated Flow